2016
DOI: 10.15406/jdhodt.2016.05.00147
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Undergraduate Dental Students at Taibah University toward Early Detection of Oral Cancer

Abstract: The aim of this study is to determine level of oral cancer awareness by assessing dental students' awareness of etiology, risk factors, diagnosis, and management of oral cancer. A total of 70 undergraduate dental students at Taibah University, from third to fifth years, enrolled in a cross-sectional study during June 2013 academic year by filling in a questionnaire assessing their knowledge of oral cancer. Data were piled up and analyzed using SPSS version 20. Our results revealed that most of students recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…Thus, the dental students should be prepared to play a part in public health awareness regarding the explanation of the potential burden of sexually transmitted viruses as HPV, in its act in oral cancer and in luence of vaccination. Most of the students preferred Oral medicine specialists when they suspect a patient with oral malignancy (Arnout, 2016) whereas in our study most of the students preferred Oncology specialists. Similar to our indings, Ahmed and Naidoo reported that most of the participants referred their patient to an oral medicine specialist, while remaining of the participants was attributed to oral and maxillofacial surgeon, general surgeon and dentists.…”
Section: Resultscontrasting
confidence: 73%
“…Thus, the dental students should be prepared to play a part in public health awareness regarding the explanation of the potential burden of sexually transmitted viruses as HPV, in its act in oral cancer and in luence of vaccination. Most of the students preferred Oral medicine specialists when they suspect a patient with oral malignancy (Arnout, 2016) whereas in our study most of the students preferred Oncology specialists. Similar to our indings, Ahmed and Naidoo reported that most of the participants referred their patient to an oral medicine specialist, while remaining of the participants was attributed to oral and maxillofacial surgeon, general surgeon and dentists.…”
Section: Resultscontrasting
confidence: 73%